Analysis of TDR Reflection Waveform for Detecting New Energy Power Cable Joint - SUN Tong; WANG Wei; WU Wei-kun; GONG Shi-ying; HE Yong; SHAN Chao (Journal of Harbin University of Science and Technology, 2022)
To solve such problems as insulation degradation of the joint of two cable segments after long-term operation in grid connection of new energy like wind energy and photovoltaic energy that requires grid-connected cables to feed energy into the main grid, it is critical that we accurately assess the health status of the joints. To study and identify the reflection waveform of cable joints under the low-voltage pulse reflection mode, the formation process of the cable joints is deduced according to the TDR (also known as the low-voltage pulse reflection method) principle. The waveform is then simulated with Simulink to work out the voltage reflection waveform of the joints. In the end, the reflection waveform of the actual cable joints is measured with the lowvoltage pulse reflection method (TDR) of the cable fault locator. The two obtain consistent wave characteristics, providing a theoretical calculation basis for automatic identification of the joint waveform and joint quality.